Covert bacteriuria in schoolchildren - Taralan Tambunan; Yuli Kumalawati; Partini P. Trihono; Astuti Giantiti; Muzal Kadim; Vera Irawani (Paediatrica Indonesiana, 2001)
Covert bacteriuria is defined as significant bacteriuria detected during a screening program, This study was done as a pari of pilot program held by Medical School University of Indonesia namely Community Health Program. The screening was carried out at four Primary School al Cibubur Subdistrict Eastern Jakarta. The population target was focused on children at the third, four1h and fifth grade from each school. Screening urinalyses include examinatiOfl for the presence of glucose, protein, blood and bacteria. There were 460 children enrolled to this study, but only 449 cases were eligible for assessment comprising 217 males and 232 females aged ranged between 7.4-14.1 years. Covert bacteriuria were found in ten cases (2.22%), comprising five males and females consecutively. Antibiotics were not given. Repeated urine culture done two weeks later revealed that six cases cured spontaneously, four other cases still showing bacteriuria although all cases remain asymptomatic. We conclude that covert bacteriuria in schoolchildren is a benign condition, most of them are spontaneously cured without antibiotic treatment. This conclusion is in accordance with the opinion of most authors that screening for bacteriuria in healthy children does not have a place in any age group including schoolchildren.